Investigating of optical device and sensing application by using photonic liquid crystal fiber - Zhang, Yifan (2013)
Photonic crystal fiber (PCF), also known as holey fiber or microstructure fiber, is characterized by the pattern arrangement of micrometer size air-holes along the length of the fiber. This microstructured waveguide is capable of guiding light by modified total internal reflection or photonic bandgap effect. The existence of the air-holes in the cladding region has opened up opportunities to introduce new materials into the fiber, allowing interactions between light and the hole-material. Because of these abilities, PCF finds their applications in varies fields, including fiber-optic communications, fiber lasers, nonlinear devices and highly sensitive gas sensors etc. One specific category of PCF is photonic bandgap fiber (PBGF), which confine light by band gap effects. Recently, the perspectives of PBG active control are further widened, due to the introduction of isotropic (refractive index oil) and anisotropic materials (liquid crystal) into the holey regions of the fibers. In this thesis, the bandgap formation and tunability after the PBGFs are filled with isotropic and anisotropic materials are studied. This thesis starts with a comprehensive review on the existing optical techniques used in optical fiber sensors. More specifically, the fundamental theory and optical fiber sensing techniques of the conventional optical fibers are reviewed. PCFs are proposed to tackle the disadvantages of conventional optical fibers, such as removing the cladding to enhance the performance. The classification and guiding mechanism of PCFs are also reviewed. Their potential advantages as optical fiber sensors are also discussed. Following that, the photonic crystal fibers for different sensing applications are investigated experimentally. Different approaches of PCF pressure sensing and Summary temperature sensing have been investigated. The results are of satisfactory. In addition, the potential of PCF air-holes coating for biomedical sensing is also numerically evaluated. Infiltrating different materials into the PCF air-holes gain different interesting features. And the interesting features are of great help in sensing applications. The introductions of isotropic material and anisotropic materials into the PCF air-holes are studied as well. The investigation of the anisotropic material mainly focuses on the nematic liquid crystal (NLC). The liquid crystal infiltrated photonic crystal fiber is called photonic liquid crystal fiber (PLCF). The temperature effect of PLCF and the electrical and optical tunabilities of PLCF have been investigated. And the applications of the PLCF have also been studied.